HUBUNGAN AKTIFTAS FISIK DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI INDOENSIA: META-ANALYSIS STUDY - Khotimah, Nurul Khusnul; Gani, Nurul Fadhila; Nurhidayah; Musdalifah; Rasmawati (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: to review using a meta-analysis approach the relationship between physical activity and blood pressure in hypertensive patients in Indonesia to find out how big the effect size correlation is for these two variables. Methods: The research used a meta-analysis research approach guided by PRISMA. There are several process stages based on PRISMA guidelines, including: Identification, Screening, eligibility and included/excluded. The research results taken are the results of research from Indonesia. So the keywords determined by researchers are "physical activity", "blood pressure" via Google Scholar. The number of studies analyzed according to the inclusion criteria was 20 cross-sectional research articles with r and n values. The researcher analyzed the data using the Jamovi application version 2.3.28. Results: Using the fixed effect model, an effect size value of -0.15 (95% CI= -0.20 to -0.10) was obtained. The results of this analysis show that there is a small effect size of the relationship between physical activity and blood pressure. The 20 studies analyzed had levels high inconsistency, namely 93,98% and no publication bias was found in this study with Egger bias value -2.657 (≥ 0.5). Conclusion: Based on It can be seen that physical activity is not the most influential factor blood pressure of hypertensive patients.